INTEGRATED MARKETING PLAN AS AN INSTRUMENT OF BRANDING OF AGRICULTURAL PRODUCTS IN THE LOCAL COMMUNITY - Kosanović, Nada; Tomaš, Mirela; Jelić, Vladimir; Popović – Vranješ, Anka (Economics of Agriculture, 2018)
Modern trends in the feld of mark business brands as the most actualized component of business activity and indicate that in this area signifcant changes are expected. The twenty-frst century will be a period in which the states will differentiate by the successful branding and marketing where intangible assets: brands, market knowledge, customer relations, distribution coverage, intellectual property, etc., will be significant value of the company. Agricultural production and food processing industries, as the main branch of the Serbian economy, have the priorities in the economic development of Serbia. The stronger performance of brand products in the markets implies the creation and promotion of Serbian brands, strategic concept of development of exportoriented agriculture, raising product quality and commitment to further liberalization of international trade.Reviving of agricultural products and areas of the Republic of Serbia in a qualitatively different starting points should have to assume the branding of the same as development potential of the Republic of Serbia and a landmark in the shaping of strategic development and national promotion of the region.